Water Sorption of Amaranthus cruentus L. Seeds Modelled by GAB Equation - Pagano, A.M. (2003)
The GAB (Guggenheim, Andersen, and de Boer) equation was adjusted to literature data of sorption of Amarunthus cruentus L. (Me vs. a w for adsorption and desorption) determined at 25,30, 35,40,45, 50, 55,65,70, and 90°C, in the range of water activity from 0.029 to 0.979. To quantify the goodness of fit, the correlation coefficient (R2), the sum of squares (RSS), the standard error of the estimate (Sy), the mean relative deviation (MRD) and the plots of residuals were analysed. The three theoretical parameters of the GAB model (Mo, C, and K) gave a good correlation (R2 > 0.9817, RSS < 0.0297, MRD < 0.138, Sy < 0.0143, and random residuals-plots) in the range of a w from 0.029 to 0.979, of interest in seed storage and processing. However this correlation does not consider the effect of temperature (T) on coefficient values. In a second stage, parameters Mo and K were adjusted at each temperature. Very low variances were obtained in the range 25-65°C for desorption and in the range 25-55°C for adsorption. These results suggested that Mo and K remain almost constant and a correlation with T is not justified. On the contrary sense, parameter C showed stronger variation with T. This was explained by the analysis of sensitivity for the influence of C on moisture content. On this basis, the relation C-T was proposed by an Arrhenius-type relation [C=A.exp(B/T)] and this function was incorporated to the original GAB model to re-estimate the parameters A, B, Mo, and K. The developed modification provides a generalised and precise expression of GAB model for Amaranth.